Efficacy and potential use of novel sustained release fillers as intracanal medicaments against Enterococcus faecalis biofilm in vitro - Bernhard Funk; David Kirmayer; Sharonit Sahar-Heft; Irith Gati; Michael Friedman; Doron Steinberg (BMC, 2019)
Abstract Background Enterococcus faecalis is a bacterium frequently isolated after failed root canal therapy. This study analyzed the antibacterial and antibiofilm effects in vitro of sustained-release fillers (SRF) containing cetylpyridinium chloride (CPC) against vancomycin resistant E. faecalis. Methods First, the solidification capability was tested by introducing liquid SRF into phosphate buffered saline, followed by 30 s of vortexing. The antimicrobial effects of SRF-CPC against static monospecies biofilms were analyzed with a metabolic assay. Inhibition of biofilm formation was tested by exposing daily refreshed E. faecalis suspensions to SRF-CPC for 9 weeks. To evaluate the effects of SRF-CPC against preformed biofilms, biofilms were grown for 1, 3 and 7 days, and then treated with SRF-CPC for 24 h. Biofilm kill time was tested by applying SRF-CPC to a 3-day-old biofilm and measuring its viability at different time points. All experiments were compared to Placebo SRFs and to untreated control biofilms. Data were analyzed with two-way ANOVA followed by Tukey's test. Results were considered significant at P < 0.05. Results The liquid SRF solidified within seconds and no structural changes were observed after 30 s of vortexing at maximum speed. SRF-CPC inhibited E. faecalis biofilm formation for 7 weeks and significantly reduced its viability in weeks 8 and 9. Mature biofilms grown for 1, 3 and 7 days were destructed by SRF-CPC in less than 24 h. Fifty percent of a 3-day-old biofilm was destructed in 2 h and complete destruction occurred in less than 12 h. (P < 0.05 in all cases, compared to SRII-Placebo). Conclusions SRF-CPC's physical properties and long-lasting anti-biofilm effects make it a promising coadjuvant medication for endodontic therapy.